Growth, Optical and Dielectric Studies on Pure and L-Lysine Doped KDP Crystals - N. Kanagathara; G. Anbalagan (International Journal of Optics)
Optically good quality single crystals of pure and L-lysine monohydrochloride-doped KDP crystals have been grown by a slow evaporation method. The grown crystals have been subjected to optical and dielectric studies. The UV-Vis spectrum shows the transmitting ability of the crystals in the entire visible region and transmittance percentage is increased for the doped KDP crystals. From the dielectric study, it is found that the dielectric constant and the dielectric loss of L-lysine-doped KDP crystals were lower than the pure KDP crystals. Hence L-lysine-doped KDP crystals are found to be more beneficial from an application point of view as compared to pure KDP crystals.